Migration in Nicaragua 2004-2009 (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
The trial aims to make a characterization, causes and economic aspects that citizens experience when deciding to emigrate. The study is descriptive and is based on the Survey of Living Standards Measurement of 2009. As a result it was found that people who emigrate to another country in search of a better life come from the urban area of 65.7% sample acquired where most out of the Pacific region with 44.1%, while men predominate to emigrate with 55.1% of the population. We conclude that the Nicaraguan migration is due to poor living conditions of survival of lowincome population, lack of resources, informal jobs, among others
Keywords: Migration residence; remittance; Region; Gender